Evaluating the effectiveness of a social and emotional learning program among preschool children in Japan: an experimental cohort study - Rikuya Hosokawa; Yuki Matsumoto; Chizuko Nishida; Keiko Funato; Aki Mitani (BMC, 2023)
Abstract Background Research on school maladjustment has increasingly focused on social skills, such as the ability to control emotions, collaborate with others, and achieve goals. Social and emotional learning (SEL) is one approach to nurturing social skills. However, few preventive interventions to promote SEL have been conducted among young children, particularly in Asian countries, including Japan. Therefore, this study examined the effectiveness of an SEL program-Fun FRIENDS-among children in Japan. Methods In mid-2022, the Fun FRIENDS program was administered to 115 children aged 4-5 years, who were enrolled in two kindergartens. The program was administered to the entire class as part of their kindergarten activities. The control group included 93 children in three kindergartens. This study included 94 participants (81.7%) in the intervention group and 66 (71.0%) in the control group, whose parents agreed with the assessment of their skills. Fun FRIENDS is a support program based on a cognitive-behavioral approach. The program aims to teach children how to cope with anxiety and stress and develop resilience and confidence to face difficulties. The program includes 10 sessions, each lasting approximately 1 h and conducted once per week. To examine the program's effectiveness, teachers evaluated these children's social skills before and after program implementation using the Social Skill Scale. Results Results showed significant post-intervention improvements in self-control and cooperation scores among children in the intervention group, compared with pre-intervention. Further, post-intervention self-control and cooperation scores were significantly higher among children in the intervention group than the control group. Conclusions SEL implemented on a class-wide basis could be effective in early childhood. An early approach targeting preschool-aged children is necessary to prevent school maladjustment. A universal approach implemented on a whole-class basis could contribute to improving children's social skills.